Good living and illicit crops in indigenous territories - Triana Sarmiento, Alejandro Enrique (2021)
Narcotraffic is one of the most stable and active businesses in the region. Because of the favorable Biosphere for the crops and the internal conflict that has promoted this activity within illegal armed groups that get revenue from the narcotraffic, Colombia has become one of the major illicit crop producers in the last decades. Illicit crops have been extended to several rural zones in Colombia, including indigenous reservations. In this article, a case of study of the Inga Aponte town is described to show how the narcotraffic affects the “Good Living” of the natives from an ethical and territorial point of view. Also, a description of how the cosmovision, institutionality, and indigenous government where key elements to motivate the natives to quit the harvests of poppy in an autonomous and sustained manner. The study concludes with the need of including the “Good Living” perspective to fight against the drugs problem in these territories.